2001
DOI: 10.1159/000054630
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Effects of Corticosterone on Splenic T-Cell Activation: Critical Role of Cell Density and Culture Time

Abstract: Glucocorticoids inhibit stimulus-induced T-cell proliferation, an early and essential parameter of cellular immunity. It was recently found however that physiological concentrations of glucocorticoids can also accelerate, not only inhibit, rat T-cell mitogenesis. We investigated mechanism(s) underlying mitogenic actions of glucocorticoids on anti-T-cell receptor (TCR)- and concanavalin A (Con A)-induced T-cell proliferation. Surprisingly, the ability of the glucocorticoid corticosterone (CORT) to either enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The authors also found a moderate inhibition of CD4 expression after 96-120 h which is consistent with our observations [19]. However, in further experiments they showed that the enhancing effect on proliferation during the first 48-72 h of culture was due to culture conditions [20]. At low densities T-cell proliferation was inhibited by corticosterone irrespective of the culture time [20].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The authors also found a moderate inhibition of CD4 expression after 96-120 h which is consistent with our observations [19]. However, in further experiments they showed that the enhancing effect on proliferation during the first 48-72 h of culture was due to culture conditions [20]. At low densities T-cell proliferation was inhibited by corticosterone irrespective of the culture time [20].…”
Section: Discussionsupporting
confidence: 88%
“…However, in further experiments they showed that the enhancing effect on proliferation during the first 48-72 h of culture was due to culture conditions [20]. At low densities T-cell proliferation was inhibited by corticosterone irrespective of the culture time [20]. Down-regulation of CD4 by dexamethasone (10 −8 to 10 −6 M) has also been described in TNF-␣-stimulated eosinophils [21].…”
Section: Discussionmentioning
confidence: 97%
“…There are numerous in vivo and in vitro reports on corticosteroids and their analogues which effect thymocyte apoptotsis and which also have adverse effects on peripheral T cell activation events. [76][77][78][79][80][81][82] However, a previous study by Wienberg et al 34 demonstrated that TREC levels increased in cord blood transplant recipients even while receiving low-dose steroids as GVHD prophylaxis. However, this data does not exclude the possibility that high dose corticosteroids used in GVHD treatment would have an adverse effect on thymic output.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies have suggested that low concentration corticosterone-induced enhancement of concanavalin A-stimulated mitogenesis of splenocytes from ADX animals may be mediated by the type-1 or mineralocorticoid receptor [77] . Finally, it was shown that corticosterone increases T-cell responsiveness to IL-2 and proliferation under conditions of high cell densities in vitro, that mimic conditions that are likely to be found in lymph nodes in vivo [78] . Thus, these in vitro studies indicate a possible mechanism by which stress and stress hormones may enhance immune function in vivo.…”
Section: Bidirectional Effects Of Glucocorticoid Hormones On Immune Fmentioning
confidence: 88%